Utilization of Artificial Intelligence as a Tool to Assist in Preparation of School Learning Materials on the West Kalimantan Border - Ristian, Uray; Ruslianto, Ikhwan; Bahri, Syamsul; Hidayati, Rahmi; Rismawan, Tedy; Suhery, Cucu; Marisa Midyanti, Dwi; Nirmala, Irma; Suhardi; Hasfani, Hirzen; Sari, Kartika; Kasliono; Muhardi, Hafiz (MEKONGGA: Jurnal Pengabdian Masyarakat, 2025)
The use of Artificial Intelligence (AI) as a tool in compiling learning materials in schools has great potential to improve the quality of education, especially in border areas that are often faced with challenges of accessibility and availability of resources. This community service activity aims to fulfill the Tri Dharma of Higher Education by providing contributions to the community while assisting teachers in utilizing AI tools. Through a preliminary study, a needs mapping was carried out together with teachers of SDN 03 Balai Karangan to ensure that the development of AI tools is relevant to learning needs on the West Kalimantan border. The development of this AI tools integrates natural language processing technology to produce learning materials that are in accordance with the curriculum and local characteristics. After development, the AI ??tools is disseminated and practiced in the school environment. It is hoped that through this activity, teachers at SDN 03 Balai Karangan on the West Kalimantan border will be better able to compile quality and relevant learning materials with the help of AI tools, can improve the quality of education and provide real benefits to local students.